2009
DOI: 10.1371/journal.pntd.0000404
|View full text |Cite
|
Sign up to set email alerts
|

Successful Interruption of Transmission of Onchocerca volvulus in the Escuintla-Guatemala Focus, Guatemala

Abstract: BackgroundElimination of onchocerciasis (river blindness) through mass administration of ivermectin in the six countries in Latin America where it is endemic is considered feasible due to the relatively small size and geographic isolation of endemic foci. We evaluated whether transmission of onchocerciasis has been interrupted in the endemic focus of Escuintla-Guatemala in Guatemala, based on World Health Organization criteria for the certification of elimination of onchocerciasis.Methodology/Principal Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…7 In field studies in Guatemala, two treatments per year have been shown to both reduce transmission and accelerate the death of adult O. volvulus worms. 33 If transmission interruption becomes a goal for Cameroon, then we strongly recommend that the MOH consider a programmatic alteration to two times per year treatment at least for Touboro (if not throughout North Cameroon), including as yet untreated hypoendemic areas adjacent to these CDTI health districts. 34 One weakness in our entomological study is that molecular testing was not performed to determine if the L3 larvae were O. volvulus or another (animal) Onchocerca species.…”
Section: Discussionmentioning
confidence: 99%
“…7 In field studies in Guatemala, two treatments per year have been shown to both reduce transmission and accelerate the death of adult O. volvulus worms. 33 If transmission interruption becomes a goal for Cameroon, then we strongly recommend that the MOH consider a programmatic alteration to two times per year treatment at least for Touboro (if not throughout North Cameroon), including as yet untreated hypoendemic areas adjacent to these CDTI health districts. 34 One weakness in our entomological study is that molecular testing was not performed to determine if the L3 larvae were O. volvulus or another (animal) Onchocerca species.…”
Section: Discussionmentioning
confidence: 99%
“…19 The infected fly rate in Abu Hamed is less than the 1 in 2,000 flies (5/10,000) threshold level used by the Onchocerciasis Control Program as an indicator for interruption of disease transmission. 20,21 This rate reflects a limit of less than 1/1,000 parous flies with a corrected level of less than 1/2,000 flies, assuming a crude parous fly rate of 50% and an infection rate of 1 infective larva per fly ( Table 1 ). 20,21 Thus the black fly infectivity rate in Abu Hamed suggests that transmission of the parasite might be close to the level below which the parasite population is unsustainable.…”
mentioning
confidence: 99%
“…20,21 This rate reflects a limit of less than 1/1,000 parous flies with a corrected level of less than 1/2,000 flies, assuming a crude parous fly rate of 50% and an infection rate of 1 infective larva per fly ( Table 1 ). 20,21 Thus the black fly infectivity rate in Abu Hamed suggests that transmission of the parasite might be close to the level below which the parasite population is unsustainable. In contrast, the Galabat focus showed black fly infectivity rate well above the threshold level, indicating continued moderate transmission of the disease in the area ( Table 1 ).…”
mentioning
confidence: 99%
“…31 In this process, an IVT country visit is undertaken after the submission by a ministry of health of a detailed dossier that provides evidence that all foci in the country have eliminated O. volvulus transmission. In Guatemala, the elimination process has already been completed and published in peer-reviewed journals for three of the four of its onchocerciasis foci: Santa Rosa, 19 Escuintla-Guatemala, 32 and Huehuetenango. 33 Based on the completion of elimination evaluations in the CEZ, as reported herein, Guatemala submitted its dossier to WHO in 2015, along with a request for an IVT visit.…”
Section: Resultsmentioning
confidence: 99%